Using hair cortisol analysis to understand the biological factors that affect black-footed ferret (Mustela nigripes) stress physiology. Issue 1 (11th May 2021) - Santymire, R M; Ali, N; Marinari, P E; Livieri, T M
Abstract : For the first time, cortisol was extracted from hair and used to compare glucocorticoid production among wild and captive black-footed ferrets. Several biological factors influenced hair cortisol concentrations including season, sex, age and location. These unique findings will assist with determining the etiology of infertility in the black-footed ferret. Abstract: The black-footed ferret ( Mustela nigripes ) was driven to near extinction due to habitat loss and an introduced disease, sylvatic plague ( Yersinia pestis ). After 35 years of breeding in ex situ facilities, the black-footed ferret has been experiencing infertility with seminal traits declining in males and only about a third of breeding-aged females are whelping. Our goal was to use hair cortisol analysis to determine if the ex situ population was experiencing chronic stress that was affecting reproduction by comparing captive ferrets to wild individuals. Our specific objectives were to (i) compare hair cortisol concentrations (HCCs) between age classes (juveniles versus adults), (ii) compare the HCCs of in situ and across different ex situ facilities and (iii) determine the relationship between HCCs and reproductive success. Overall, wild juveniles had higher HCC than wild adults. Our generalized linear mixed model determined that the parameters that best predict HCC for adults were the interactions among sex, in situ versus ex situ facilities and season. During both seasons, wild females had higher HCCs compared to the ex situ females. During the breeding season, male HCCs across breeding facilities varied and males at the breeding facility with the largest ferret habitats had HCCs similar to wild males. At one breeding facility, HCC was higher in males that sired compared to those that did not sire. In conclusion, ex situ ferrets do not have higher HCC than wild individuals when controlling for season and ex situ habitat size, and ex situ males with higher HCC tended to sire. This suggests that HCC may be metabolically driven and/or that low HCC may be an indication of hypothalamus–pituitary–adrenal axis dysregulation and warrants further investigation both for laboratory validation and biological relevance.